2002
DOI: 10.2139/ssrn.846305
|View full text |Cite
|
Sign up to set email alerts
|

Asset Prices, Financial and Monetary Stability: Exploring the Nexus

Abstract: BIS Working Papers are written by members of the Monetary and Economic Department of the Bank for International Settlements, and from time to time by other economists, and are published by the Bank. The papers are on subjects of topical interest and are technical in character. The views expressed in them are those of their authors and not necessarily the views of the BIS.This working paper was written for the Conference on "Changes in risk through time: measurement and policy options" that took place at the BI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
785
2
23

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,012 publications
(866 citation statements)
references
References 36 publications
34
785
2
23
Order By: Relevance
“…Rules that stabilize the price level, however, are commonly thought to lessen the chance of asset price bubbles (e.g., Woodford, 2003). Some economists argue, however, that a commitment to low inflation can foster imbalances that lead to asset price bubbles by generating overly optimistic expectations of future economic growth (e.g., Borio and Lowe, 2002). Federal Reserve Chairman Alan Greenspan made this claim at a Federal Open Market Committee (FOMC) meeting in 1996:…”
Section: A R C H / a P R I L 2 0 0 7 F E D E R A L R E S E R V E B mentioning
confidence: 99%
“…Rules that stabilize the price level, however, are commonly thought to lessen the chance of asset price bubbles (e.g., Woodford, 2003). Some economists argue, however, that a commitment to low inflation can foster imbalances that lead to asset price bubbles by generating overly optimistic expectations of future economic growth (e.g., Borio and Lowe, 2002). Federal Reserve Chairman Alan Greenspan made this claim at a Federal Open Market Committee (FOMC) meeting in 1996:…”
Section: A R C H / a P R I L 2 0 0 7 F E D E R A L R E S E R V E B mentioning
confidence: 99%
“…Indeed empirical works provide mixed results and findings depend on selected countries and historical periods under consideration (Stock & Watson, 1999;Dwyer & Hafer, 1999;Trecroci & Vega-Croissier, 2000;Leeper & Roush, 2002). On a specific note, many studies have concluded that, significant money stock expansions that are not coupled with sustained credit increases are less likely to have inflationary consequences (Bordo & Jeanne, 2002;Borio & Lowe, 2002;Borio and Lowe, 2004;Detken & Smets, 2004; Van den Noord, 2006;Roffia & Zaghini, 2008;Bhaduri & Durai, 2012). This position could be particularly questionable in Africa, given the high surplus liquidity issues the financial system of the continent is facing.…”
Section: Introductionmentioning
confidence: 99%
“…According to international experiences, the corresponding phases in asset price cycles and credit cycles are prone to aligning with each other, and when that happens, the cyclical positions are greater than on average (Claessens et al 2011). Furthermore, asset price bubbles that are linked to excessive lending are more likely to end in a financial crisis (Borio -Lowe 2002) and entail greater losses for the real economy (Brunnermeier -Schnabel 2015;Jordà et al 2015) than those that are not coupled with excessive lending. Furthermore, the dangerous mix of excessive lending and asset price bubbles can emerge relatively easily if one of them is already present (in the case of properties see: Anundsen -Jansen 2013: Tables 1 and 2; Mian -Sufi 2011).…”
Section: The Role Of Excessive Lendingmentioning
confidence: 99%